Pengaruh Bauran Pemasaran Terhadap Keputusan Berkunjung di Agrowisata - yuliana samantha; Tuti Gantini; Suci Nurhaeni (Jurnal Penelitian Pertanian Terapan, 2024)
This study aims to find out the diversity and application of marketing mix in Edu-Agrotourism Lembang Terrace and to find out the effect of marketing mix variables (product, price, place, promotion, person, process, and physical evidence) on the decision to visit agrotourism both simultaneously and partially. This study used descriptive and verification methods with quantitative approaches. Structural Equation Modeling (SEM) with research instruments is used in the form of questionnaires. The number of study samples of 60 respondents with the sampling technique used is probability sampling by the simple random sampling method. Research results show that simultaneous test results of marketing mix variables (product, price, place, promotion, person, process, and physical evidence) together have a positive and significant effect on visiting decisions. Partial test results show that promotional variables (X4) and physical evidence (X7) have a significant effect on visiting decisions, while product variables (X1), price (X2), place (X3), person (X5), and process (X6) have an insignificant effect on visiting decisions at Edu-Agrotourism Lembang Terrace. Keywords: Marketing Mix, Visiting Decisions, Edu-Agro-Tourism